2019
DOI: 10.1002/ece3.5523
|View full text |Cite
|
Sign up to set email alerts
|

Grassland harvesting alters ant community trophic structure: An isotopic study in tallgrass prairies

Abstract: Disturbances have long been recognized as important forces for structuring natural communities but their effects on trophic structure are not well understood, particularly in terrestrial systems. This is in part because quantifying trophic linkages is a challenge, especially for small organisms with cryptic feeding behaviors such as insects, and often relies on conducting labor‐intensive feeding trials or extensive observations in the field. In this study, we used stable isotopes of carbon and nitrogen to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 66 publications
(118 reference statements)
1
9
0
Order By: Relevance
“…In tropical forests, for example, generalist ants display a similar pattern to the pavement ants in our study, shifting upward in trophic level in disturbed environments that contain fewer plant-feeding hemipterans (Blüthgen et al, 2003;Woodcock et al, 2013). But generalist ants in other habitats may become less predatory in more disturbed or less diverse environments (Gibb & Cunningham, 2011;Kim et al, 2019;Resasco et al, 2012) or may not shift trophic position in response to disturbance (Tanaka et al, 2019). Although our results reflect changes in resource use, other factors may contribute to apparent trophic shifts in animals.…”
Section: Trophic Ecologysupporting
confidence: 59%
See 2 more Smart Citations
“…In tropical forests, for example, generalist ants display a similar pattern to the pavement ants in our study, shifting upward in trophic level in disturbed environments that contain fewer plant-feeding hemipterans (Blüthgen et al, 2003;Woodcock et al, 2013). But generalist ants in other habitats may become less predatory in more disturbed or less diverse environments (Gibb & Cunningham, 2011;Kim et al, 2019;Resasco et al, 2012) or may not shift trophic position in response to disturbance (Tanaka et al, 2019). Although our results reflect changes in resource use, other factors may contribute to apparent trophic shifts in animals.…”
Section: Trophic Ecologysupporting
confidence: 59%
“…In tropical forests, for example, generalist ants display a similar pattern to the pavement ants in our study, shifting upward in trophic level in disturbed environments that contain fewer plant‐feeding hemipterans (Blüthgen et al., 2003; Woodcock et al., 2013). But generalist ants in other habitats may become less predatory in more disturbed or less diverse environments (Gibb & Cunningham, 2011; Kim et al., 2019; Resasco et al., 2012) or may not shift trophic position in response to disturbance (Tanaka et al., 2019). Dietary specialists show a similar range of responses, either not varying their trophic position with plant richness or disturbance (predatory trap‐jaw ants Odontomachus bauri , Duyck et al., 2011) or becoming less predatory in more disturbed environments (seed harvesters Pogonomyrmex badius , Smith & Suarez, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, previous work at this site showed that ants are flexible in their trophic breadth and position (Kim et al. 2019). High rates of seed predation also suggest that ants have abundant resources at this site (Wenninger et al.…”
Section: Discussionmentioning
confidence: 97%
“…However, it is possible that ant predation on decomposers is a relatively minor part of the overall flow of matter and energy in these grasslands because ants rely on multiple food sources (King 2016). For example, previous work at this site showed that ants are flexible in their trophic breadth and position (Kim et al 2019). High rates of seed predation also suggest that ants have abundant resources at this site (Wenninger et al 2016) and may be leaning more toward herbivory than predation.…”
Section: No Effects Of Ant Suppression On Decomposition and Decomposersmentioning
confidence: 92%